Dampak Digitalisasi Terhadap Pertumbuhan UMKM di Negara Berkembang - Hastin Umi Anisah; Nadila Lea Friska; Mahdi Hidayatullah (Jurnal Riset dan Inovasi Manajemen, 2024)
Digitalization has become a crucial factor in enhancing the competitiveness and growth of Micro, Small, and Medium Enterprises (MSMEs) in developing countries, particularly within the ASEAN region. This study aims to explore the impact of digitalization on MSME growth in Indonesia, the Philippines, and Vietnam through a Systematic Literature Review (SLR) approach. These three countries were selected due to their substantial economic potential and evolving levels of technology adoption, yet each faces unique challenges in digital transformation. The study analyzes literature on the role of digitalization in improving market access, operational efficiency, and MSME financing, identifying key drivers and barriers specific to each country. Findings reveal that digitalization significantly contributes to enhancing productivity and sustainability for MSMEs, though challenges related to infrastructure, digital literacy, and regulatory frameworks present notable obstacles. This review aims to provide insights for policymakers and MSME stakeholders in optimizing digitalization strategies to foster economic growth in ASEAN.